2021
DOI: 10.1021/acs.nanolett.0c03593
|View full text |Cite
|
Sign up to set email alerts
|

Halide Perovskite Semiconductor Lasers: Materials, Cavity Design, and Low Threshold

Abstract: Solution-processable semiconductor lasers have been a long-standing challenge for next-generation displays, light sources, and communication technologies. Metal halide perovskites, which combine the advantages of inorganic and organic semiconductors, have recently emerged not only as excellent candidates for solution-processable lasers but also as potential complementary gain materials for filling the “green gap” and supplement industrial nanolasers based on classic II–VI/III–V semiconductors. Numerous perovsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
214
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(229 citation statements)
references
References 80 publications
0
214
1
1
Order By: Relevance
“…Low-dimensional perovskites have also shown huge potential in the lasing field, including edge-emitting amplified spontaneous emission (ASE), vertical-cavity surface-emitting lasers (VCSELs), miniature laser, polaron laser and so on. 135 Xiong et al 136 demonstrated for the first time lasing based on the whisperinggallery-mode (WGM) optical resonant cavity with the hexagonal and triangular shapes of MAPbI 3 . Fu et al 137 used 2D perovskite (BA) 2 (MA) n-1 PbBr 3n+1 to fabricate a WGM laser using polydimethylsiloxane (PDMS) template.…”
Section: Nanolasersmentioning
confidence: 99%
“…Low-dimensional perovskites have also shown huge potential in the lasing field, including edge-emitting amplified spontaneous emission (ASE), vertical-cavity surface-emitting lasers (VCSELs), miniature laser, polaron laser and so on. 135 Xiong et al 136 demonstrated for the first time lasing based on the whisperinggallery-mode (WGM) optical resonant cavity with the hexagonal and triangular shapes of MAPbI 3 . Fu et al 137 used 2D perovskite (BA) 2 (MA) n-1 PbBr 3n+1 to fabricate a WGM laser using polydimethylsiloxane (PDMS) template.…”
Section: Nanolasersmentioning
confidence: 99%
“…[1][2][3][4] At the same time, the high fluorescence yield, high gain, and wavelength tunability make LHP an ideal materials for optoelectronics research, such as light-emitting devices and lasers. [5][6][7][8][9] Numerous reports have demonstrated lasing actions in LHP including organicinorganic hybrid perovskites [6,7,10] or all-inorganic perovskites [11][12][13] in Fabry-Perot cavity, [7,10] whisper gallery cavity, [14] or distributed feedback (DFB) cavity [15] operated on plasmonic mode, [16][17][18] photonic mode, [6,7,15,19] and even polariton mode [20,21] from low temperature to room temperature or even higher. However, the lasing mechanism in LHP is still under investigation, even though various mechanisms have been proposed to explain how lasing happens.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25–28 ] The strong coupling of exciton and light field produces energy–momentum anticrossing dispersion in the microcavity. [ 25,29 ]…”
Section: Resultsmentioning
confidence: 99%